Identification of Growth-Related Gene BAMBI and Analysis of Gene Structure and Function in the Pacific White Shrimp Litopenaeus vannamei - Ruigang Niu; Xiaojun Zhang; Yang Yu; Zhenning Bao; Junqing Yang; Jianbo Yuan; Fuhua Li (Animals, 2024)
As one of the most important aquaculture species in the world, the improvement of growth traits of the Pacific white shrimp (Litopenaeus vannamei), has always been a primary focus. In this study, we conducted SNP-specific locus analysis and identified a growth-related gene, BAMBI, in L. vannamei. We analyzed the structure and function of LvBAMBI using genomic, transcriptomic, metabolomic, and RNA interference (RNAi) assays. The LvBAMBI possessed highly conserved structural domains and widely expressed in various tissues. Knockdown of LvBAMBI significantly inhibited the gain of body length and weight of the shrimp, underscoring its role as a growth-promoting factor. Specifically, knockdown of LvBAMBI resulted in a significant downregulation of genes involved in lipid metabolism, protein synthesis, catabolism and transport, and immunity. Conversely, genes related to glucose metabolism exhibited significant upregulations. Analysis of differential metabolites (DMs) in metabolomics further revealed that LvBAMBI knockdown may primarily affect shrimp growth by regulating biological processes related to lipid and glucose metabolism. These results suggested that LvBAMBI plays a crucial role in regulating lipid metabolism, glucose metabolism, and protein transport in shrimp. This study provides valuable insights for future research and utilization of BAMBI genes in shrimp and crustaceans.